A 6-month trial of memantine for nystagmus and associated phenomena in oculopalatal tremor - Martins, Ana Inês; Soares-dos-Reis, Ricardo; Jorge, André; Duque, Cristina; Pereira, Daniela Jardim; Fontes Ribeiro, Carlos; Sargento-Freitas, João; Matos, Anabela; Negrão, Luís; Lemos, João (Frontiers in Neurology, 2022)
Introduction: Oculopalatal tremor (OPT) is a late manifestation of a Guillain-Mollaret triangle lesion. Memantine has been shown to improve nystagmus in OPT, but its long-term efficacy and putative distinct effects on each plane of nystagmus and on associated phenomena are largely unknown. Methods: We conducted a 6-month open-label study to evaluate the effect of memantine in OPT patients. Baseline (visit 1), 2 (visit 2) and 6 months (visit 3) assessments included video-oculography, best corrected visual acuity (BCVA), visual function questionnaire (VFQ25), palatal tremor frequency and subjective visual vertical (SVV). Memantine was titrated to 20mg per day and stopped after 6 months. Results: We included 6 patients (5 females; mean age 68.5+/-9.7). At visit 2, nystagmus improved >50% only along the horizontal plane in 2 patients, while worsening >50% along the vertical plane in 4 patients. At visit 3, previous improvement of nystagmus along the horizontal plane in 2 patients was not sustained, and further worsened >50% along the vertical plane in 4. Mean vertical velocity and amplitude of nystagmus in the left eye significantly worsened from visit 2 to visit 3 (p=0.028). Throughout the study, nystagmus frequency remained unchanged (p=0.074), BCVA improved in both eyes (p=0.047, p=0.017), SVV progression was unpredictable (p=0.513), and mean VFQ-25 score (p=0.223) and mean palatal frequency remained unchanged. Conclusion: The long-term use of memantine 20mg per day in OPT produced a modest and only transient improvement of nystagmus, predominantly along the horizontal plane. Visual acuity improved, albeit without relevant changes in vision-related quality of life.